The Extra-Ordinary Music Camp: An informal online distance learning approach for children with intellectual and physical disabilities and learning disorders - Després, Jean-Philippe; Julien-Gauthier, Francine; Jourdan-Ionescu, Colette; Bédard-Bruyère, Flavie (Frontiers in Education, 2022)
In summer 2020, 25 children aged 8 to 17 with intellectual and physical disabilities and learning disorders participated in a research project called the Extra-Ordinary Music Camp. The objectives were to (1) provide an adapted environment where extra-ordinary children could develop musical creativity; and (2) examine the impact of informal, inclusive, participatory, and adapted creative music activities on specific development areas. Individual 20- to 40-minute online sessions were delivered at a distance biweekly for seven weeks. Mixed methods analysis was used to determine the effects. Results show shared improvement across the communication and social skills measures, and improvements for all participants in community use, musical skills, autonomy, and technology skills. Notably, the improvements in community use (ABAS-II) and communication (specifically developed questionnaire) were significant.